Manganese for Whom? A Review on Manganese Mining Permits towards the Existence of Springs’ Sacred Forest in Manggarai Flores - Steni, Bernadinus; Kartodihardjo , Hariadi; Adiwibowo , Soeryo; Djakapermana , Ruchyat Deni (Forest and Society, 2025)
Amid global efforts to find minerals for renewable energy, social-environmental concerns related to mineral extraction are still ongoing. Various agreements at the global level are calling for the renewable energies market to uphold principles of sustainability throughout the entire supply chain, including raw materials extraction, to protect the integrity and objectives of the industry. Importantly, such action must extend beyond the narrow parameters of environmental management to inclusively consider impacts on community wellbeing as well. This article evaluates concerns around land and spring conversion in manganese mining operations in Manggarai, Flores, East Nusa Tenggara Province, NTT. The study is critical to designing a bridging model of water institutional development at the district level that would help realize the water rights of the villagers toward actual action. The analysis of how water institutions function in villages is an area of study that has not been widely examined in Indonesia, even though water issues are increasingly prominent in many regions. This article seeks to analyze functioning water institutions using institutional critical analysis. We apply spatial analysis to mining operation areas to identify land use contestations between mines and the springs as well as settlements. The analysis integrates in-depth interviews with the officials from three key government institutions related to land uses and the springs. Both the spatial analysis and qualitative data are then analyzed alongside the legal framework of land use and spring used to distill the institutional barriers leading to the issuance of permits in such contexts. The analysis then briefly traces the current political economy of mining’s permits underlying the institutional interactions to better understand why the institutions behave as they do. Ultimately, the study finds that mining operations occur in spaces with common resources of sacred springs and settlements. Even though the overlapping was deemed illegal by state law, causes such as poor institutional authority over spring governance, economic rather than social-based motivations for reviewing permits, and election incentives drive institutional behavior, not simply law. In light of this, the study concludes that springs-related institutions at the district level are at a crossroads regarding whether to protect the springs due to the changes in several laws, including regional government law in 2014. However, the expectation of economic growth, local politics, and global demand for manganese remains a significant underlying influence of allocating permits to manganese mines.